# Calculus

posted by Mike

Solve using chain rule

y=(3x^3+1)(-4x^2-3)^4

So far, I have:

y'=(3x^3+1)*4(-4x^2-3)^3*(-8x)+(-4x^2-3)^4*(9x^2)

1. Damon

fine so far

## Similar Questions

1. ### Math - Calculus Question.

hey can someone explain to me the relationship between the chain rule and implicit differentiation?
2. ### Calculus

How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?
3. ### calculus

I have been asked to solve this two different ways. The first way is to use the chain rule and then simplify (which I have already done properly), and the second way is to simplify and then differentiate (not necessarily with the chain …
4. ### calculus

Let z = ∫(e^sin(t)dt) from x to y a = x b = y I tried thinking about it like a chain rule but even then i'm a little unsure. I know dz/dt = e^sin(t). Can you please point me in the right direction if i'm supposed to use the chain …
5. ### calculus

Let z = ∫e^(sin(t))dt from x to y a = x b = y I tried thinking about it like a chain rule but even then i'm a little unsure. I know dz/dt = e^(sin(t)). Can you please point me in the right direction if i'm supposed to use the …
6. ### calculus

Let z = ∫e^(sin(t))dt from x to y a = x b = y I tried thinking about it like a chain rule but even then i'm a little unsure. I know dz/dt = e^(sin(t)). Can you please point me in the right direction if i'm supposed to use the …
7. ### calculus

Find dz/dy and dz/dx Let z = ∫e^(sin(t))dt from x to y a = x b = y I tried thinking about it like a chain rule but even then i'm a little unsure. I know dz/dt = e^(sin(t)). Can you please point me in the right direction if i'm …
8. ### Calculus

can you show me how to solve an equation using the chain rule